Patient access to records: expectations of hospital doctors and experiences of cancer patients. - Fisher, B (1993)
The aim of this study was to examine cancer patients' reactions to the offer of access to their medical records, hospital doctors' preconceptions of patient access to medical records and the reality of access to records for both parties. Semistructured interviews were conducted with 32 patients and 21 hospital doctors. Hospital doctors were also shown letters from their department to the general practitioner and asked about any changes they would have made as a result of knowing about patient access to records. The results showed that most patients were able to judge for themselves if they wanted access or not and that patients who chose to look at their records found access to their records helpful and reassuring even if the news was bad. Doctors expected access to records to be harmful to patients but would not have wished to amend many of the letters they had written. Patient access to records can be a safe and useful adjunct to good patient care.